Coaching youth gymnastics - American sport education program with USA Gymnastics - Feldmann, K.; Galimore, L. (Human Kinetics, 2011)
The book covers all the basics of coaching and gymnastics in a concise style that is customized for entry-level gymnastics coaches. Developed by ASEP in cooperation with USA Gymnastics, this one-of-a-kind book offers a unique blend of general coaching and sport-specific information. Included are Coaching Tips boxes that highlight key concepts, in addition to information on developing a coaching philosophy, communicating with athletes and parents, and providing basic sport first aid. The latest information regarding concussions and CDC protocols is also addressed. The book contains forms and safety checklists and sample lesson and practice plans. Techniques and skills for bars, floor, beam, and vault are presented by skill level rather than by age groups and are applicable to both boys and girls where appropriate. Information on falling and landing as well as suggestions on activities, conditioning, and games are provided. The expertise of USA Gymnastics and ASEP's proven success in coaching education will ensure an adequate preparation for the challenges of coaching youth gymnastics. With content aimed at developing the entire coach, not just skills and drills, "Coaching Youth Gymnastics "will help to create an environment that promotes learning, enjoyment, safety, and motivation for youth gymnasts.